Manajemen Proyek Rekayasa Perangkat Lunak Aplikasi Reservasi Meeting Room Berbasis Website - Tri Hartati; Noer Hikmah; Leliyanah Leliyanah (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Meetings are an activity carried out by a group of elite businesspeople to plan business steps for the company's progress to overcome business obstacles and achieve significant profits. However, sometimes holding offline meetings is still hampered by the lack of rooms that do not match the desired number and conditions. The main factors that become obstacles are the lack of information on the availability of meeting rooms from several vendor options in strategic locations and difficulties in the manual reservation process. The purpose of this research is to conduct a project management engineering application for meeting room reservations to help elite businesspeople find meeting rooms that meet their criteria by involving several vendors in strategic locations. The software engineering method used is waterfall, which consists of the stages of requirements, system analysis, design, implementation, testing and debugging of the application to be developed. The expected result of this research is a project management design in the development of a website-based meeting room application that can help elite businesspeople in finding meeting rooms that meet their criteria so that their business can run smoothly.